Socialization of the Goals and Functions of Islamic Religious Education in Labuhanbatu Regency South - Harahap, Aziddin; Syahputra Harahap, Hasmi; Andrianto, Richi; Harahap, Arman (CV. Inara, 2024)
Education is a process carried out consciously or deliberately in order to increase knowledge, insight and experience to determine life goals so that they can have a broad view towards a better future and with education itself can create quality human beings. Like Western theory, educators in Islam are people who are responsible for the development of students by trying to develop all students' potential, both affective (feelings), cognitive (creativity), and psychomotor potential (intentions). Education is a cultural process to improve human dignity that lasts throughout life. Education is always developing, and is always faced with changing times. That is the cycle of development of changes in education, otherwise education will be left behind by the rapid changes of the times. For this reason, changes in education must be relevant to changing times and the needs of society at that time, so it is important to plan as early as possible which can be stated in the Vision, Mission, Goals and Functions of Islamic Education.